Evaluation of the relationships between psychiatric comorbidity and seizure semiology in psychogenic non-epileptic seizure patients - Gülce Coşku Yılmaz; Hatice Sabiha Türe; Esin Evren Kılıçaslan; Galip Akhan (Acta Psychologica)
Psychogenic non-epileptic seizures (PNES) are episodic events that bear a resemblance to epileptic seizures (ES) in their outward manifestations, yet they lack pathological electroencephalographic (EEG) activity during the ictal phase. In the Diagnostic and Statistical Manual 5th Edition (DSM-5), PNES is designated as ''Functional Neurological Symptom Disorder with seizures''. Individuals diagnosed with PNES commonly present with concurrent psychiatric disorders, notably depression, panic disorder, and chronic anxiety. This phenomenon renders PNES a shared affliction within the domains of neurology and psychiatry, thereby mandating the implementation of diverse therapeutic approaches in the management of the condition. Indeed, identifying the presence of concurrent psychiatric disorders in a patient with PNES during the early stages is crucial for devising an appropriate treatment plan.In this study, an assessment was conducted to examine the correlation between PNES semiology and psychiatric disorder comorbidity, to elucidate whether semiological characteristics serve as predictors for the presence of comorbid psychiatric disorders. The PNES patients enrolled were divided into two subgroups based on the presence or absence of accompanying psychiatric disorders (onlyPNES and PNES+). The study assessed disparities in semiological characteristics between the two subgroups of PNES and the results obtained indicate that individual variations in semiotic features are not influenced by the presence of psychiatric comorbidity.